Analisis Penerapan Indikator Global Reporting Initiative (GRI) Pada Laporan Tahunan dan Laporan Keberlanjutan Perusahaan Pertanian - Riantri Barus; Febriyana Silalahi; Sri Fajar Ayu (Jurnal Akademi Akuntansi, 2024)
Purpose: The purpose of this study is to analyze the level of disclosure of GRI indicators in sustainability reports for agricultural companies listed on the Indonesia Stock Exchange, analyze differences in the level of disclosure of GRI indicators in sustainability reports for agricultural companies listed on the Indonesia Stock Exchange in 2014 and 2020, and analyze the effect of size, profitability, and the size of the board of commissioners on the disclosure of sustainability reports on agricultural companies listed on the Indonesia Stock Exchange. Methodology/approach: The research was conducted on agricultural companies listed on the Indonesia Stock Exchange using purposive sampling, with the criteria being registered during the 2014 - 2020 period, publishing financial reports for the 2014 and 2020 periods, and publishing annual reports for the 2014 and 2020 periods. Data analysis used the descriptive method, content analysis, paired sample t-test, and multiple linear regression. Findings: The results of the study show that the level of disclosure of GRI indicators in the sustainability reports of agricultural companies listed on the Indonesia Stock Exchange in 2014 was 33.4%, while in 2020 it was 51.1%. There is a significant difference in the level of GRI indicator disclosure in the sustainability reports of agricultural companies listed on the Indonesia Stock Exchange in 2014 and 2020. Profitability and board size have a significant positive effect on sustainability report disclosure in agricultural companies listed on the Indonesia Stock Exchange, but company size has no effect.  Practical and Theoretical Contribution/Originality: The difference between this study and previous studies is that it compares the level of disclosure in 2014 with 2020, where 2014 was the year when the GRI index began to be used. Research Limitation: The variables used are still limited to indicators in financial reports. For further research, certification variables in the agricultural sector can be added.